2022
DOI: 10.3389/fendo.2022.855326
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Approach in Adrenal Surgery: Retroperitoneoscopic Partial Adrenalectomy

Abstract: The interest on partial adrenalectomy has steadily increased over the past twenty years. Adrenal pathologies are mostly benign, making an organ-preserving procedure attractive for many patients. The introduction of minimally invasive techniques played probably an important role in this process because they transformed a complex surgical procedure, related to the difficult access to the retroperitoneal space, into a simple operation improving the accessibility to this organ. In this review we summarize the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Less blood loss and shorter operative times during adrenal partial procedures have been reported when compared with whole-organ removal [ 40 , 42 ]. Alesina et al [ 13 ] suggested that PA should always be contemplated in case of PHEO, especially when considering that familial diseases account, nowadays, for almost 40% of all cases. Kawasaki et al [ 43 ] applied PA surgery for MEN2A PHEOs, whereas for MEN2B, bilateral TA was performed based on their experience of stronger association with multicentricity and aggressive behavior in such cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Less blood loss and shorter operative times during adrenal partial procedures have been reported when compared with whole-organ removal [ 40 , 42 ]. Alesina et al [ 13 ] suggested that PA should always be contemplated in case of PHEO, especially when considering that familial diseases account, nowadays, for almost 40% of all cases. Kawasaki et al [ 43 ] applied PA surgery for MEN2A PHEOs, whereas for MEN2B, bilateral TA was performed based on their experience of stronger association with multicentricity and aggressive behavior in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid, or at least reduce, the need for life-long corticosteroid therapy, partial adrenalectomy (PA) has been proposed as a valuable alternative to TA. This approach is based on three assumptions: infrequency of malignant PHEO in some inherited syndromes, acceptable risk of recurrence (7% over 3 years and 10–15% over 10 years) and high likelihood of corticosteroid independence [ 8 , 13 ]. Risk of recurrence in such cases seems to be of lesser significance when compared to the morbidity and mortality of adrenal insufficiency, consequent lifelong hormone replacement and its deleterious effect on puberty and quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, two new drugs were approved by the FDA, levoketoconazole and osilodrostat, which are both inhibitors of steroidogenic enzyme activity. Non-functioning adrenal tumors are evaluated to verify eligibility for partial adrenalectomy based on size and potential to malignancy ( 229 ). In general, surgery should be considered in lesions >4cm in size or those that are hormonally indeterminate, even if imaging characteristics resemble those of a benign lesion ( 50 ).…”
Section: Treatment Approaches and Clinical Trialsmentioning
confidence: 99%